The Advancements and Future of Regenerative Medicine - Akram, Muhammad; Rehman, Urooj; Umaru, Isaac John (African Journal of Clinical Medicine and Pharmacy Research, 2025)
The sector of healthcare is witnessing new advancements in the field of Regenerative Medicine as it aims to provide treatment options for previously considered unsolvable cases. Scientists are seeking ways through stem cell therapy, gene editing, and tissue engineering to restore or replace damaged tissues and organs. Stem cell therapy is a key player by creating tissues from non specialized cells. Tissue engineering and amplification of 3D bioprinting biomaterials allow the production of synthetic organs and therefore lessen the demand for actual organ donors. The use of CRISPR-Cas9 as a gene editing tool opens new opportunities for treating genetic issues such as cystic fibrosis or sickle cell anemia. The main challenge lies in the enormous expenditure, bureaucracy, ethics, and program rejection difficulty. Although these things slow the expansion of the methods to clinics, further deeper studying gives hope for the medicine to fully change the paradigm caring more about curing than relieving symptoms. The funds and innovations that go into regenerative therapies may prove one day to be the answer to millions globally.